Discovery of eRASSt J192932.9-560346: A bright, two-pole accreting, eclipsing polar - Schwope, Axel; Buckley, David A. H.; Malyali, Adam; Potter, Stephen; König, Ole; Arcodia, Riccardo; Gromadzki, Mariusz; Rau, Arne (Astronomy & Astrophysics, 2022)
We report the discovery of a bright (V similar to 15), eclipsing, two-pole accreting magnetic cataclysmic variable (CV), a polar, as counterpart of the SRG/eROSITA and Gaia transients eRASStJ192932.9-560346 and Gaia21bxo. Frequent large-amplitude changes of its brightness at X-ray and optical wavelengths by more than four magnitudes are indicative of a CV nature of the source. Identification spectra obtained with the 10m SALT telescope revealed the typical features of a magnetic CV: strong, broad HeI, HeII, and hydrogen Balmer emission lines superposed on a blue continuum. Time-resolved photoelectric polarimetry revealed that the circular polarization varies from -20 to +20% and the linear polarization varies from 0 to 10%, confirming the system to be a magnetic CV of the polar subclass. High-cadence photometry revealed deep, structured eclipses, indicating that the system is a two-pole accretor. The orbital period determined from the eclipse times is 92.5094 +/- 0.0002 min. The X-ray spectrum is thermal only, and the implied luminosity is L-X = 2.2 x 10(31) erg s(-1) at the Gaia-determined distance of 376 pc.
CRIS-Team WoS Importer:2022-06-17